A CRITICAL APPRAISAL OF PARTI ISLAM SEMALAYSIA (PAS) OPPOSITION-BASED STRUGGLE FOR AN ISLAMIC STATE (UNTIL 2008) - Ahmad Fauzi Abdul Hamid (Media Syari'ah, 2017)
The shattering defeat of PAS in the 2004 general elections, while holding on to the reins of government in the state of Kelantan by a tiny majority, heralded an era of introspection for party leaders and strategists. PAS had misread popular sentiment for justice and good governance, which had propelled it into recording massive gains at the expense of its arch-rival UMNO in 1999, as an endorsement of its Islamic state agenda. Its adamant retention of this agenda, costing it an alliance with the Democratic Action Party (DAP) in the Barisan Alternatif (BA) coalition, was most vividly displayed by its revelation of the Islamic State Document (ISD) in late 2003. While PAS does not claim to have disavowed the ISD, deliberations on the ISD seem to have stalled in preference for internal party reforms. Prodding for the reforms are the young professionals whose influx into the party in the mid-1990s transformed the landscape of PAS which in the 1960s was closely identified with the Malay peasantry class. Clearly, the impact of globalization and the rise of the middle class during the era of Dr. Mahathir Mohamad’s Premiership have not eluded PAS. This paper traces such changes, focusing on the realms of political economy and ideological modernization. Internal pressures for changes have accelerated since the electoral setback of 2004 and a string of by-election defeats, at the risk of alienating grassroots party activists who hold the conservative ulama leadership in high esteem. This paper contends that any structural transformation in PAS will necessarily take a long time. Internal fissures are not automatically solved by electoral success, as experienced by PAS in the March 2008 elections, when PAS not only retained the state of Kelantan, but also shared the spoils of power in Kedah, Perak, Selangor and Penang as a component party of the newly assembled People’s Pact (PR: Pakatan Rakyat) coalition.